Internal Marketing Practices For Sustainable Development of The RMG Industry of Bangladesh - Sarbabidya, Surajit (European Publisher, 2019)
Beginning with less standard workplace, under trained and less skilled employees for poor compensation, etc., to the gradual improvement into customer-centric business growth, social and environmental compliance through internally motivated skilled employees altogether indicate a great progress towards the sustainable development of the RMG industry in Bangladesh. However, the industry is yet to reach its full potentials. From this perspective, the current study is an attempt to examine the relationship between ‘Internal Marketing’ practices and ‘Sustainable Development’ of the RMG industry of Bangladesh. The current paper is the result of both primary and secondary data collection which internationally published prominent findings. While primary data have been collected from the sample size of 140 respondents including staffs and officials of RMG factories. Inferential statistical tools have been used for the analysis of the collected primary data. The findings of the current study indicate a good number of ‘Internal Marketing’ practices including employee survey to listen to their grievances, consultation with employees or their representatives, inclusive culture of encouraging diversity and equal employment opportunity, women empowerment, treating employees fairly and with respect, training and development programs for employees, rewarding the excellent performers, compliance with local legislation, etc., so that sustainable development of the RMG industry of Bangladesh can be ensured.